ReCLAIM – Restoring Coastal Landscape for Adaptation Integrated Mitigation - Center for International Forestry Research (2021)
The Restoring Coastal Landscape for Adaptation Integrated Mitigation (ReCLAIM) Project is a collaborative effort between the Center for International Forestry Research (CIFOR) and various Indonesian partners representing university, government agenceis, and civil society with support from the David and Lucile Packard Foundation, USA.